2019
DOI: 10.1017/s1368980018003816
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in a multi-ethnic population of northern Norway: the SAMINOR 2 Clinical Survey

Abstract: ObjectiveTo investigate serum 25-hydroxyvitamin D (S-25(OH)D) concentration in a multi-ethnic population of northern Norway and determine predictors of S-25(OH)D, including Sami ethnicity.DesignCross-sectional data from the second survey of the Population-based Study on Health and Living Conditions in Regions with Sami and Norwegian Populations (the SAMINOR 2 Clinical Survey, 2012–2014). S-25(OH)D was measured by the IDS-iSYS 25-Hydroxy Vitamin Dˢ assay. Daily dietary intake was assessed using an FFQ. BMI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 55 publications
1
27
0
4
Order By: Relevance
“…Additionally, studies have shown that diet, and especially vitamin D, can affect gingivitis . Both smoking and obesity have been associated with lower levels of vitamin D in a population‐based study in Northern Norway . Finally, the host‐dependent variation in gingivitis susceptibility should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies have shown that diet, and especially vitamin D, can affect gingivitis . Both smoking and obesity have been associated with lower levels of vitamin D in a population‐based study in Northern Norway . Finally, the host‐dependent variation in gingivitis susceptibility should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Both smoking and obesity have been associated with lower levels of vitamin D in a population-based study in Northern Norway. 52 Finally, the host-dependent variation in gingivitis susceptibility should be considered. In several studies, a subject-specific gingival inflammatory response has been reported, and "high and low responders" 53 or "fast and slow responders" were identified.…”
Section: F I G U R Ementioning
confidence: 99%
“…This is substantiated by work in the Inuit population of Greenland, where there was a marked increase in vitamin D deficiency alongside a decrease in traditional diet, overall36 and particularly among the younger age groups of the population 37. Similar results have been seen in the far north of Norway,38 where diet rich in vitamin D-containing foods was associated with vitamin D status, but this behaviour was less common among younger participants. While substantiation of this hypothesis would require a systematic longitudinal survey of diet behaviours across the Scandinavian region and across its latitudinal range, this would still seem to be the most plausible interpretation, as we suggested in our previous paper 1…”
Section: Discussionmentioning
confidence: 53%
“…From other studies, it is known that fish intake is the most influential food source contributor to vitamin D intake [52,53], and there may be a strong correlation between fatty fish intake and 25(OH)D levels [54]. A recent cross-sectional Norwegian study revealed that for a median vitamin D intake of 10.3 µg, the mean 25(OH)D level was 64.0 nmol/L, while the prevalence of deficiency (defined as 25(OH)D < 50 nmol/L) was only 24.7%; in such a situation, a low vitamin D deficiency prevalence was observed, even in winter [55]. This suggests that with an adequate vitamin D intake (at least 10 µg/day) it is possible to achieve an adequate 25(OH)D level, maybe even in seasons with limited sunshine exposure such as the autumn and winter seasons in Poland.…”
Section: Discussionmentioning
confidence: 99%